Argon Laser Peripheral Iridoplasty for Primary Angle-Closure Glaucoma: A Randomized Controlled Trial - Narayanaswamy, Arun; Baskaran, Mani; Perera, Shamira A; Nongpiur, Monisha E; Htoon, Hla M; Tun, Tin A; Wong, Tina T; Goh, David; Su, Daniel H; Chew, Paul T K; Ho, Ching-Lin; Aung, Tin (Ophthalmology (Rochester, Minn.), 2016)
To determine the effectiveness of argon laser peripheral iridoplasty (ALPI) in primary angle closure (PAC) and primary angle-closure glaucoma (PACG). Randomized controlled trial. Eighty PAC or PACG subjects who underwent laser iridotomy (LI) and had at least 180° of persistent appositional angle closure and intraocular pressure (IOP) of more than 21 mmHg were enrolled. Subjects were randomized to receive either 360° ALPI (Visulas 532s; Carl Zeiss Meditec, Jena, Germany) or medical therapy (Travoprost 0.004%; Alcon-Couvreur, Puurs, Antwerp, Belgium). Repeat ALPI was performed if the IOP reduction was less than 20% from baseline along with inadequate angle widening at the month 1 or month 3 visit. Intraocular pressure was controlled with systematic addition of medications when required. The primary outcome measure was success rates after ALPI at 1 year. Complete success was defined as an IOP of 21 mmHg or less without medication, and qualified success was defined as an IOP of 21 mmHg or less with medication. Failure was defined as an IOP more than 21 mmHg despite additional medications or requiring glaucoma surgery. Forty subjects (51 eyes) were randomized to ALPI and 40 subjects (55 eyes) were randomized to medical therapy. Complete success (IOP ≤21 mmHg without medication) was achieved in 35.0% eyes of the ALPI group compared with 85.0% of eyes in the prostaglandin analog (PGA) group (P < 0.001), and qualified success (IOP ≤21 mmHg with medication) was achieved in 35.0% and 7.5%, respectively (P = 0.003). The IOP decreased by 4.9 mmHg (95% confidence interval [CI], 3.5-6.3 mmHg) in the ALPI group (P < 0.001) and by 6.1 mmHg (95% CI, 5.1-7.1 mmHg) in the medication group (P < 0.001). A failure rate of 30.0% was noted in the ALPI group compared with 7.5% in the medication group (P = 0.01). No treatment-related complications were recorded in either group. After 1 year, ALPI was associated with higher failure rates and lower IOP reduction compared with PGA therapy in eyes with persistent appositional angle closure and raised IOP after LI.